Designable Al32‐Oxo Clusters with Hydrotalcite‐like Structures: Snapshots of Boundary Hydrolysis and Optical Limiting - Liu, Ya‐Jie; Li, Qiao‐Hong; Li, De‐Jing; Zhang, Xue‐Zhen; Fang, Wei‐Hui; Zhang, Jian (Angewandte Chemie International Edition, 2021)
The hydrolysis of earth‐abundant AlIII has implications in mineral mimicry, geochemistry and environmental chemistry. Third‐order nonlinear optical (NLO) materials are important in modern chemistry due to their extensive optical applications. The assembly of AlIII ions with π‐conjugated carboxylate ligands is carried out and the hydrolysis and NLO properties of the resultant material are studied. A series of Al32‐oxo clusters with hydrotalcite‐like cores and π‐conjugated shells are isolated. X‐ray diffraction revealed boundary hydrolysis occurs at the equatorially unsaturated coordination sites of AlIII ions. Charge distribution analysis and DFT calculations support the proposed boundary substitution. The Al32‐oxo clusters possess a significant reverse saturable absorption (RSA) response with a minimal normalized transmittance up to 29 %, indicating they are suitable candidates for optical limiting (OL) materials. This work elucidates the hydrolysis of AlIII and provides insight into layered materials that also have strong boundary activity at the edges or corners. A series of Al32‐oxo clusters with hydrotalcite‐like cores and π‐conjugated shells were isolated, which are unique models of two‐dimensional or layered materials and may be used to study boundary activity and optical limiting properties.